Rendimiento forrajero y calidad del ensilaje de canavalia en monocultivo y asociada con maíz - Ortiz G. Sanín; Cortés R. Harry; Jimenez Paola A (Acta Agronómica)
Mediante un modelo experimental completamente al azar con tres tratamientos y cinco repeticiones se determinaron los cambios en la producción de forraje verde disponible (FVD) producción de materia seca (MS) y la relación de material de alto valor forrajero (MAVF) vs tallos. El rendimiento por corte de FVD para canavalia fue de 43.18 ± 4.6., para maíz de 39.23 ± 7.3, y para la asociación de 47.27 ± 7.9 t/ha/corte. No se presentaron diferencias significativas (P< 0.05 ) entre los tratamientos en rendimiento de MS. La producción anual de MS fue de 45.64, 47.88 y 49.64 t/ha/año. Se presentaron diferencias significativas (P< 0.05) entre tratamientos en la relación MAVF Vs tallos obteniéndose la mejor relación en canavalia. La asociación en forraje verde y en ensilaje superó en PC y FDN al FVD de maíz. La conservación mejoró la calidad del FVD en los tres tratamientos.

ABSTRACT

Forage yield and nutricional quality of canavalia silage on pure cultivation and intercroping system. A full random experimental model with three treatments and five repeat, were determined the changes of chemical composition of cultivation alone and intercropping systems of canavalia and corn . The yield of DGF for canavalia and corn alone was of 43.18 ± 4.6 and 39.23 ± 7.3 t/ha/harvest, respectively; for the association was of 47.27 ± 7.9 t/ha/harvests. Not presented significant differences (P <0.05) among the treatments as for dry matter (DM). The production estimated in DM of canavalia, corn and the association was 45.64, 47.88 and 49.64 t/ha/year respectively. It was presented significant differences (P <0.05) among the treatments as for relationship of high value forage Vs. shafts being obtained the best relationship in the canavalia. The association as much in green forage as in silage was superior in CP, NDF and available green forage (AGF) that the corn like and silage. The conservation process improved the quality of the AGF for the three treatments.

Key words: Canavalia ensiformis, Zea mays, intercroping systems, nutricional quality, silage, NDF, CP, AGF.